2015
DOI: 10.9771/gmed.v7i2.15169
|View full text |Cite
|
Sign up to set email alerts
|

Trabalho, Educação E Reprodução Em Lukács

Abstract: Resumo: Este artigo é resultado de pesquisa que teve como objetivo analisar as contribuições de György Lukács para se compreender o trabalho, a educação e a sociedade como indispensáveis para a reprodução do gênero humano. Destacamos, a partir do estudo, duas formas de pores teleológicos: pores que realizam a transformação da natureza pelo trabalho, e pores que se propõem a exercer influência sobre a consciência de outros homens, os quais se realizam pelas práxis sociais. Conclui-se que a educação é uma práxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
4
4
0
2
Order By: Relevance
“…Our research ndings revealed that 6.9% of students reported having used sedatives and sleeping pills at some point in their lives, with 4.6% indicating recent usage within the past three months. It is noteworthy that our study's results closely align with those reported by Fes and Meknes universities (19), where the lifetime usage rate was found to be 5.1%. This similarity suggests a consistent pattern within the national context.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our research ndings revealed that 6.9% of students reported having used sedatives and sleeping pills at some point in their lives, with 4.6% indicating recent usage within the past three months. It is noteworthy that our study's results closely align with those reported by Fes and Meknes universities (19), where the lifetime usage rate was found to be 5.1%. This similarity suggests a consistent pattern within the national context.…”
Section: Discussionsupporting
confidence: 91%
“…After conducting the univariate analysis, it became evident that there was a signi cant correlation between the consumption of psychoactive substances and male gender (P < 0.0001), as well as age over 20 years (P < 0.0001). These associations have been consistently reported in previous studies (18,19,30,33,34), suggesting a robust pattern. The reasons behind these associations can be attributed to diverse social and cultural factors that tend to normalize substance consumption among men more than women and among young adults more than adolescents.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations